2016
DOI: 10.1177/1473325016668962
|View full text |Cite
|
Sign up to set email alerts
|

Between a rock and a softer place—A discourse analysis of helping cultures in crisis resolution teams

Abstract: The main aim of this thesis was to explore experiences of helpful help in mental health crises within the context of crisis resolution teams (CRTs). Helpful help has been explored from three different perspectives: 1) service users, 2) carers, and 3) CRT clinicians. These perspectives are represented through three different sub-studies in this thesis. The study included a strategic sample of participants recruited from eight different health trusts, geographically covering large parts of Norway. Individual int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Creative and collaborative help and support is considered important to recovery-oriented practices. Klevan and colleagues found that helpful help was experienced as something creative and ‘in the making’ [ 53 ]. This is in contrast to a predetermined and defined approach to helping and supporting.…”
Section: Resultsmentioning
confidence: 99%
“…Creative and collaborative help and support is considered important to recovery-oriented practices. Klevan and colleagues found that helpful help was experienced as something creative and ‘in the making’ [ 53 ]. This is in contrast to a predetermined and defined approach to helping and supporting.…”
Section: Resultsmentioning
confidence: 99%
“…However, I find myself nodding in agreement with Rita’s assertion that stories about human misery give meaning to distress experiences, and that the act of listening and telling is dialogical and relational, aimed at empowering the person who is telling their story and being listened to (Klevan, Karlsson, Ness, Grant, & Ruud, 2016). But I still don’t have much of a handle on what Rita’s implicit narrative (Richardson, 1997, 2001) is around what she takes for granted in writing about mental health issues, and whether this fits with mine.…”
Section: Alec: June 21 2017mentioning
confidence: 59%
“…This includes not only having expert skills in assessing acute mental distress and suicide risk but also having skills and capacity to inform a more collaborative and interprofessional approach to crises. As such, the expectations for collaboration with CRTs are diverse, reflecting the diverse rationale for CRTs, comprising components related to effectiveness and cost reduction and more value-based components related to contributing to humanizing mental health services (Klevan et al, 2018;Wheeler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%